2002
DOI: 10.1177/152692480201200306
|View full text |Cite
|
Sign up to set email alerts
|

A Multiethnic Study of the Relationship between Fears and Concerns and Refusal Rates

Abstract: This study builds on previous research that identified fears and concerns heard by procurement coordinators during the donation discussion and that classified those concerns according to the ease with which they can be addressed. In this study, 53 coordinators working for 4 procurement agencies provided data on 323 donation discussions, including fears and concerns expressed by families. The fears and concerns were analyzed by outcome (consent or refusal), race and ethnicity of the family, frequency of reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…18 Unfortunately, studies have shown Hispanics to be more likely than other groups to refuse to donate the organs of a recently deceased loved one. [19][20][21] Organ donation among Hispanics undoubtedly needs to increase, and several steps have been taken in this direction. [22][23][24] Our earlier research suggests that living organ donation may be a practical alternative for Hispanics because Alvaro et al they hold positive attitudes about living organ donation and suggests that these attitudes are significant predictors of their intentions to become living donors.…”
Section: Living Organ Donation and Hispanicsmentioning
confidence: 99%
“…18 Unfortunately, studies have shown Hispanics to be more likely than other groups to refuse to donate the organs of a recently deceased loved one. [19][20][21] Organ donation among Hispanics undoubtedly needs to increase, and several steps have been taken in this direction. [22][23][24] Our earlier research suggests that living organ donation may be a practical alternative for Hispanics because Alvaro et al they hold positive attitudes about living organ donation and suggests that these attitudes are significant predictors of their intentions to become living donors.…”
Section: Living Organ Donation and Hispanicsmentioning
confidence: 99%
“…African American donation rates are significantly lower than Hispanic donation rates, 1,5 the only other minority for which we have good consent rate data. The reasons for these relatively low donation rates have generated a great deal of debate and go beyond the scope of this paper.…”
Section: African Americansmentioning
confidence: 77%
“…Other recommendations for working with African American families can be found in a recent article by Siminoff et al, 5 but fall outside the scope of this paper because they were derived from research, not from African Am erican participants in our workshops. However, related to the findings in that research, many African American participants have pointed out that concerns and anger that African Americans may express in the donation conversation are often linked to the treatment they receive while their loved one is in the hospital.…”
Section: Hispanic Peoplementioning
confidence: 99%
“…Hmong culture aside, data show that donor families more broadly have fears that vary by ethnicity, especially within minority populations. 17 Precedent exists for parents' permitting the procurement of only specified organs for deceased donation from their child. We identified a case in the literature in which a Jehovah's Witness family allowed their deceased child to be an organ donor; however, they allowed only her liver and kidneys to be donated but not her heart.…”
Section: Discussionmentioning
confidence: 99%